Contribution of Ockham's logic to fourteenth century's philosophy - Francisco, Alyson Bueno [UNESP] (Pontificia Univ Catolica Parana, 2023)
William of Ockham was an English philosopher of the fourteenth century with contributions to the logic of terms and the nominalist movement, marked by the critical sense of the Early Middle Ages by post-Thomism. In the Middle Ages, the conceptualist discourse of Peter Abelard generated problems of use of beings and universals, with Ockham being the philosopher who advocated the method of not using entities for generalizations or hasty conclusions, known as Ockham's razor. This article presents the contributions of the logic of terms and objectivity in Ockham's philosophy. As specific analyses of the stages presented in the article, we have the contribution to the scientific method by the use of the concept of incomplex knowledge, formed by intuition and abstraction in the singularity. The emphasis of the logic of terms structured in the work Summa of Logic, developed the parsimonious language by propositions, whose philosopher defends the terms in the school of nominalism. In the development of the logic of terms, Ockham presents the theory of assumption, being considered a position by some other object, and can be classified into: personal, determined, confusing or distributive. The use of logic with objectivity ensured the criticism of the universals that were used at the time as innate ideas, synthesizing an objective method to avoid repetitions of terms called by contemporaries by razor. Despite being against the repetition of terms in the medieval discourse of universals, Ockham considers the need for repetition of experienced facts to record events, the future of which can be predicted by the possibility of repetition of events that occurred in the past. In summary, Ockham's contribution to the logic of the late Middle Ages is incontrovertible.
Keywords: Contribution of Ockham's logic to fourteenth century's philosophy; Intuition; Logic of terms; Singular